Evidence for Horizontal Gene Transfer in Evolution of Elongation Factor Tu in Enterococci - Ke, Danbing (American Society for Microbiology, 2000)
The elongation factor Tu, encoded by tuf genes, is a GTP binding protein that plays a central role in protein synthesis. One to three tuf genes per genome are present, depending on the bacterial species. Most low-G+C-content gram-positive bacteria carry only one tuf gene. We have designed degenerate PCR primers derived from consensus sequences of the tuf gene to amplify partial tuf sequences from 17 enterococcal species and other phylogenetically related species. The amplified DNA fragments were sequenced either by direct sequencing or by sequencing cloned inserts containing putative amplicons. Two different tuf genes (tufA and tufB) were found in 11 enterococcal species, including Enterococcus avium, Enterococcus casseliflavus, Enterococcus dispar, Enterococcus durans, Enterococcus faecium, Enterococcus gallinarum, Enterococcus hirae, Enterococcus malodoratus, Enterococcus mundtii, Enterococcus pseudoavium, and Enterococcus raffinosus. For the other six enterococcal species (Enterococcus cecorum, Enterococcus columbae, Enterococcus faecalis, Enterococcus sulfureus, Enterococcus saccharolyticus, and Enterococcus solitarius), only the tufA gene was present. Based on 16S rRNA gene sequence analysis, the 11 species having two tuf genes all have a common ancestor, while the six species having only one copy diverged from the enterococcal lineage before that common ancestor. The presence of one or two copies of the tuf gene in enterococci was confirmed by Southern hybridization. Phylogenetic analysis of tuf sequences demonstrated that the enterococcal tufA gene branches with the Bacillus, Listeria, and Staphylococcus genera, while the enterococcal tufB gene clusters with the genera Streptococcus and Lactococcus. Primary structure analysis showed that four amino acid residues encoded within the sequenced regions are conserved and unique to the enterococcal tufB genes and the tuf genes of streptococci and Lactococcus lactis. The data suggest that an ancestral streptococcus or a streptococcus-related species may have horizontally transferred a tuf gene to the common ancestor of the 11 enterococcal species which now carry two tuf genes.